EFFECTIVE WAYS OF LEARNING ENGLISH GRAMMAR: TO EXPLOIT CORRECTLY INFINITIVE AND GERUND - Zubaydova Nilufar Ne’matullayevna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this article, the person explores the peculiarities of the infinitive and gerund and also the proper use of them. The article describes the cases in which the horse-specific forms of the verb occur, as well as the differences and similarities.